Satisfaction Analysis of Museum Bank Indonesia Visitors using Integration Importance-Performance Analysis (IPA) and Kano Model - Prasetya, Wibawa; Putri (Dinasti Publisher, 2024)
At In this era, museum paradigm is having a growth from traditional museum paradigm to paradigm of new museology. New museology offers active role and also participation of visitor in the Museum but new museology concept is not much implemented in Indonesian museums. By always improving service quality will improve the satisfaction of visitors which will impact on visitor’s interest or visitor’s participation towards museum. This research is intended to analyze visitor’s satisfaction towards service quality given by museum. This research is done by using non-probability sampling which is purposive sampling. Integration of Importance Performance Analysis and Kano Model is used in this research so it can analyze the satisfaction of museum visitors with 30 testing indicators. The results of this research shows that there is indicators that was not proper with visitor’s demands which is the ability of officers to explain collections and promotion that had been done. Even though those indicators influences satisfaction of museum visitors, therefore museum must do more evaluation towards its service and to follow the state of technology nowadays.